Early relationships of adolescents: Evaluation and observation of romantic attachment and risk behavior. (May 2014) - Letcher, Amber; Slesnick, Natasha
The purpose of the study was to examine the relationship between attachment behavior, substance use, and sexual activity among adolescents in romantic relationships. Concepts from attachment theory have been proposed to explain adolescent risk behavior; however, research on adolescent attachment rarely assesses both members of the couple. A total of 21 adolescent couples (aged 15–18 years) were assessed on self-report and observed measures of romantic attachment, substance use, and sexual activity. Attachment anxiety was related to one's own risk behavior. Self-reported attachment avoidance was also related to one's own and his/her partner's observed attachment behaviors. Given these results, risk prevention/intervention programs targeted toward adolescents may benefit from assessing attachment representations of adolescents, which may be related to participation in risk behavior.